94.3k views
1 vote
Given f(x)=-8x+4 and g(x) = x^2, choose the expression for (f*g)(x)

Given f(x)=-8x+4 and g(x) = x^2, choose the expression for (f*g)(x)-example-1
User Spider Man
by
6.0k points

1 Answer

2 votes

ANSWER


(f\circ g)(x) = - 8 {x}^(2) + 4

Step-by-step explanation

Given f(x)=-8x+4

and

g(x)=x²

We want to find find an expression for;


</p><p>(f\circ g)(x) = f(g(x))


</p><p>(f\circ g)(x) = f( {x}^(2) )

We substitute x² into f(x)=-8x+4

This will give us:


</p><p>(f\circ g)(x) = - 8 {x}^(2) + 4

User Smaug
by
5.8k points